Venture Capital Fund-a Partner of Development of SMES and It Firms for an Economically Developed Digital Bangladesh - Akter, Shahanaz; Jahangir Alam, Dr. Mohammad (International Journal of Scientific Research and Management (IJSRM), 2020)
For the development of any country, the development f economy is crucial and for the development of economy nourishment and proper burgeon of the business must be ensured. Bangladesh has recently stepped up to the “Developing” ranking and aiming for sustainable development. Entrepreneurship had been the most important contributor in economic development interms of employment,innovations and healthy market competition over the last decades.As such, Entrepreneurship is the primary factor in the development of economies. A new business always affects the people and the economy of the locality as a new opportunity gets created for employment, earnings and better living standard. A new business in a local area may engender other related business and transactions. For example, an opening of a new branch of the bank may inspire the entrepreneurs of that area to implement their business plans. The Theory of Kirzner (1973-2005) about entrepreneurship explains how the improvement of economic health affects individuals in the first world. It is needless to say, how the development of services such as roads, public transportations, health, education, and entertainment are backed by the growth of industries and companies in various fields. The implementation of those industrial activities resulted in the development of a more vibrant economy.As such, for an economy to operate smoothly and to be in a good state, it highly depends on the Financial Institutions which assists to keep economy hydrated. Hence, a regular and even flow of fund encourages business development or entrepreneurship and operations which ensure economic growth. In Bangladesh, there are Banks and Non-Banking Financial Institutions for this very purpose. But there come some limitationsunder the decision-making system of these institutions when the subject customer is new entrepreneurship or developing or Greenfield Company, which has high growth potential as well as high risk of default. Therefore,there is still a gap between the required fund for any new business and actual funds that can be disbursed from Banks and NBFIs.Venture Capital is a category of equity or debt finance or combination of both which is generally offered to entrepreneurs and small companies, which bear high growth potential but also prone to high risk. Venture capital funds differ from the other investment companies as the others try to limit their risk-taking actions up to a specified ceiling with specified rules and guidelines made by the company articles of association and memorandum of association and management principlesgoverned bythe board.Even though Venture Capital is a still-developing concept in Bangladesh as a vital source of funds and assistance, it is already a popular way of business development for developed countries. This paper is aimed to discuss the prospect of Venture Capital in Bangladesh and how this financing assists as co-entrepreneur of start-ups and growing ventures speciallyfor the sector of SMEs and IT.